Meningkatkan Kemandirian Belajar Materi Manusia Makhluk Pribadi Dengan Metode PBL Kelas X SMKN 1 Singkawang - Bernadus Ridan (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Not all of the students who were accepted at Singkawang 1 Public Vocational School were in accordance with their main choices causing low learning independence and learning achievement, so they did not reach KKTP, namely 75. This study aims to: 1) Knowing the increase in learning independence in the subject of human beings being private class X at SMK Negeri 1 Singkawang. 2) Knowing the effectiveness of the PBL method in increasing student learning outcomes in class X personal human beings at SMK Negeri 1 Singkawang. This study applies a quantitative descriptive approach, namely making descriptive of a situation objectively using numbers, starting from data collection, interpretation and display of the results. The research design was Classroom Action Research which was conducted in two (2) cycles, of class X students with a population of 12 people. The results showed that 1) PBL can increase learning independence in material for class X human beings at Singkawang State Vocational School 1. It can be seen that the average independence from 69.94 increased to 78.87%. 2) PBL is effective in increasing student learning outcomes in class X human beings personal material at SMK Negeri 1 Singkawang. It can be seen that 0% is proficient, 66.67% competent and 33.33% proficient, increasing to 66.67% proficient, 16.67% proficient and 16.67% proficient. Thus it can be concluded that the PBL method is effective in increasing independence and learning achievement.